2021
DOI: 10.1111/jvp.12981
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of neomycin sulfate after intravenous and oral administrations in swine

Abstract: The aminoglycoside antibiotic neomycin, which is used to treat external or internal bacterial infections, is primarily administered in veterinary medicine as a sulfate salt. However, no information is available on the pharmacokinetic characteristics and absolute availability of neomycin sulfate after intravenous (i.v.) and oral (p.o.) administrations in swine. Here, these parameters were studied in swine after i.v. and p.o. doses of single 15 mg/kg body weight doses. The blood samples were assessed using ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…When we tested the response of FX40-37-FQ with cDNA-9B to 100 μM interferents, we observed minimal cross-reactivity except in the case of quinine, neomycin, chlorpromazine, ractopamine, and ciprofloxacin, which had ≥25% cross-reactivity relative to 10 μM flunixin (Figure B). This is problematic in the case of neomycin and ciprofloxacin, as these drugs are commonly administered in livestock, and their concentrations tend to be in the micromolar range in blood shortly after treatment. …”
Section: Resultsmentioning
confidence: 99%
“…When we tested the response of FX40-37-FQ with cDNA-9B to 100 μM interferents, we observed minimal cross-reactivity except in the case of quinine, neomycin, chlorpromazine, ractopamine, and ciprofloxacin, which had ≥25% cross-reactivity relative to 10 μM flunixin (Figure B). This is problematic in the case of neomycin and ciprofloxacin, as these drugs are commonly administered in livestock, and their concentrations tend to be in the micromolar range in blood shortly after treatment. …”
Section: Resultsmentioning
confidence: 99%
“…It may also be used orally or in combination with other antibiotics to treat certain gastrointestinal infections. Pharmacokinetic studies have revealed that the active compound exhibits a relatively short plasma half-life of 3–4 h [ 28 ]. However, it is rapidly absorbed in the intestinal tract, suggesting its suitability for utilization in controlled-release formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Neomycin is poorly absorbed after oral administration, is to a large extent excreted in the faeces (> 90%) and remains primarily as the parent compound. A recent study showed that the neomycin elimination half-life in pigs after oral administration is long (12.43 ± 7.63 h at 15 mg/kg bodyweight) and the absolute bioavailability is low [3]. By using a single high dose of 50,000 IU/kg bodyweight, we can utilise the pharmacokinetic properties of the drug while also reducing the total amount of neomycin used to treat each pig.…”
Section: Introductionmentioning
confidence: 99%